(untitled) (Linguostylistic Studies, 2016)
The article highlights the peculiarities of inflection of neuter gender nouns formed on the model of the old substantives with *-ǒ-, *-jǒ-stems. The emphasis is laid on the factors affecting the existence of dialect differences in the inflectional system under the analysis. The author argues the specifics of dialectal paradigm of the analyzed nouns and concludes that they are determined by the intensive processes of innovative character, including phonetic patterns typical for dialects and grammatical analogy. The study singles out the productivity of the phonetically modified old former inflections of the substantives with *-ǒ-,*-jǒ-stems. The remains of doubling plural forms of neuter nouns in the nominative and the accusative cases are interpreted as expressive/emphatic morphological archaisms. The illustrative examples of variant actualization of every specific ending in one dialect clearly testify that the process of establishing inflectional dialect standards is still in progress. Key words: patois, form inflections, noun, case, flexion, grammatical analogy, phonetic innovation. References